Government-market synergy in China's agricultural low-carbon transformation: policy adaptation to regional divides - Liao, Feng; Zheng, Yangyang; Wang, Xiaofeng; Xiong, Lihui (Frontiers in Sustainable Food Systems, 2025)
IntroductionPromoting agricultural low-carbon transformation are essential for achieving the “dual carbon” targets and advancing high-quality development.MethodsThis study employed evolutionary game theory to construct a tripartite model involving local governments, agricultural enterprises, and consumers. It stimulated their decision-making processes and explored the mechanisms of the government and market. Furthermore, taking into account regional technological differences, this study examined the differentiated incentive effects of two mechanisms, and developed a comprehensive analytical framework for agricultural low-carbon transformation.Results(1) The model revealed three evolutionarily stable states, with the system evolving toward the optimal equilibrium of (1,1,1) under specific constraint conditions. (2) To achieve the system's Pareto optimality, the optimal intervals for subsidy coefficients and carbon emission penalties were (0.2, 0.25) and (1.5, 1.75), respectively. The optimal intervals for publicity coefficients and low-carbon consumption preferences were (0.3, 0.35) and (0.65, 0.7), respectively. (3) Considering regional technological differences, western regions with lower levels of low-carbon technology should prioritize government regulation, supplemented by market adjustment. Central regions should strike a balance between two methods, whereas eastern regions with more advanced low-carbon technologies should focus on market adjustment, with government regulation as a supplement.DiscussionThis study enhances the understanding of the mechanisms underlying the government and market, holding both theoretical and practical significance for advancing agricultural low-carbon transformation.